An objective evaluation of fundamental pharmacogenomics knowledge among pharmacists and pharmacy students - Mira Mehtar; Safaa H. Hammoud; Mohamed Ezzat Khamis Amin (Elsevier, 2022)
Introduction: Possessing a correct and comprehensive foundation on the science of pharmacogenomics (PGx) is an important prerequisite for pharmacists to successfully apply pharmacogenomic testing to patient care. While some work has addressed general PGx knowledge among pharmacists, little research has specifically focused on PGx foundational knowledge. This study examines the level of foundational knowledge of PGx and interest in learning about PGx among community pharmacists and first-year pharmacy students at Beirut Arab University (BAU), Beirut, Lebanon. Methods: A cross-sectional survey was self-administered to community pharmacists within a random sample of community pharmacies in Beirut, Lebanon, and to first-year BAU pharmacy students. The knowledge component of the instrument consisted of 25 items, each worth one point, addressing fundamental PGx information. The validity and internal consistency of the designed instrument were tested among the study population. Correlation analysis was carried out between aggregate knowledge and key variables for participating pharmacists. Results: Of 150 approached pharmacists, 137 (91 %) participated and of 132 pharmacy students, 131 (99 %) participated. The average knowledge score for community pharmacists was 15 (Standard Deviation = 4) out of a possible total of 25 with the total number of correct answers ranging from 8 to 24 out of 25 questions. The average score for pharmacy students was 17 (Standard Deviation = 5) out of a possible total of 25 with the total number of correct answers ranging from 5 to 24. Pharmacists' age and years of practice were associated with a lower aggregate knowledge score (r = −0.20; p < 0.05 and r = −0.21; p < 0.05), respectively. Pharmacists' interest in learning about PGx varied whereas 62 % were either interested or very interested in learning about PGx. Students' interest, however, was higher with 70 % being either interested or very interested. Specific PGx topics of interest to participants were highlighted. Conclusion: This study identified areas where PGx foundational knowledge was acceptable and others where significant opportunities for improvement exist. These results add to the rapidly expanding field of pharmacogenomics education and practice in relation to pharmacy. In particular, these findings have significant implications for planning pharmacogenomics-related educational activities targeting current and future pharmacists.